Pengaruh Produksi Jagung, Harga Jagung dan Kurs Dollar Terhadap Impor Jagung Indonesia - Sri Mahmuji; Reza Juanda (Jurnal Ekonomi Pertanian Unimal, 2024)
This research aims to determine the effect of corn production, corn prices,0, and the dollar exchange rate on corn imports in Indonesia for the period 1991-2022. This research uses data for 1991-2022 obtained from the Food and Agriculture Organization (FAO). The Vector Error Correction Model (VECM) is the data analysis method. The research results show that in the short-term corn production does not affect Indonesian corn imports. In contrast, corn prices and the dollar exchange rate negatively and significantly affect Indonesian corn imports. Meanwhile, in the long term, corn production positively and significantly affects Indonesian imports. In contrast, corn prices and the dollar exchange rate significantly negatively impact Indonesian corn imports.